2021
DOI: 10.1016/j.ijcha.2021.100832
|View full text |Cite
|
Sign up to set email alerts
|

‘Routine’ versus ‘Smart Phone Application Based – Intense’ follow up of patients with acute coronary syndrome undergoing percutaneous coronary intervention: Impact on clinical outcomes and patient satisfaction

Abstract: Highlights Smart phone application use in follow up of post intervention acute coronary syndrome patients. This could individualize each patients follow up and shown higher satisfaction and comparable clinical outcomes. This should be explored further for long term benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The analysis showed that studies on the use of mobile applications were conducted in the USA (n=7) ( 30 - 36 ), Sweden (n=3) ( 37 - 39 ), Republic of Korea (n=1) ( 40 ), Brazil (n=1) ( 41 ), Norway (n=2) ( 42 , 43 ), Switzerland (n=1) ( 44 ), Belgium (n=1) ( 45 ), China (n=9) ( 22 , 46 - 53 ), Romania (n=1) ( 54 ), Japan (n=1) ( 55 ), Finland (n=1) ( 24 ), France (n=1) ( 56 ), New Zealand (n=1) ( 57 ), Iran (n=2) ( 58 , 59 ), Georgia (n=1) ( 60 ), Spain (n=2) ( 61 , 62 ), Palestine (n=1) ( 63 ) and Germany (n=3) ( 64 - 66 ). Two studies were conducted simultaneously in India (n=2) ( 67 , 68 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis showed that studies on the use of mobile applications were conducted in the USA (n=7) ( 30 - 36 ), Sweden (n=3) ( 37 - 39 ), Republic of Korea (n=1) ( 40 ), Brazil (n=1) ( 41 ), Norway (n=2) ( 42 , 43 ), Switzerland (n=1) ( 44 ), Belgium (n=1) ( 45 ), China (n=9) ( 22 , 46 - 53 ), Romania (n=1) ( 54 ), Japan (n=1) ( 55 ), Finland (n=1) ( 24 ), France (n=1) ( 56 ), New Zealand (n=1) ( 57 ), Iran (n=2) ( 58 , 59 ), Georgia (n=1) ( 60 ), Spain (n=2) ( 61 , 62 ), Palestine (n=1) ( 63 ) and Germany (n=3) ( 64 - 66 ). Two studies were conducted simultaneously in India (n=2) ( 67 , 68 ).…”
Section: Resultsmentioning
confidence: 99%
“…By category, the research was focused on the following areas: mobile applications for diagnostic purposes (for example, ECG recording ( 30 ), assessment of heart rate ( 31 , 33 , 44 , 65 ). Some studies were carried out to validate the system for urgent care alarm ( 37 ), lifestyle changes ( 43 , 45 , 53 , 62 , 65 ), adherence to treatment ( 35 , 38 , 41 , 47 , 48 , 51 , 53 , 55 , 59 , 60 , 63 , 64 , 67 , 68 ), and physical activity of the patients ( 22 , 32 , 34 , 41 , 45 , 62 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After removing duplicate studies, the remaining 2979 records were screened. After reading 41 eligible full-text articles, 22 were excluded, and 19 were selected [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. A summary of the study characteristics and participant demographics are presented in Multimedia Appendix 3 [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Identification Of Studiesmentioning
confidence: 99%
“…In this systematic review, we assessed the impact of eHealth interventions on cardiac surgery recovery based on the results of 19 studies. These studies reported at least an equal (n=6) [29,30,33,38,39,42] or positive effect (n=13) [31,32,[34][35][36][37]40,41,[43][44][45][46][47] of the eHealth intervention compared to conventional care. According to the results of the meta-analysis, when compared with the control group, the eHealth intervention group showed an improvement in both the physical component of quality of life and the depressive status of patients after cardiac surgery.…”
Section: Principal Findingsmentioning
confidence: 99%